2013
DOI: 10.1002/adma.201301034
|View full text |Cite
|
Sign up to set email alerts
|

Clay: New Opportunities for Tissue Regeneration and Biomaterial Design

Abstract: Seminal recent studies that have shed new light on the remarkable properties of clay interactions suggest unexplored opportunities for biomaterial design and regenerative medicine. Here, recent conceptual and technological developments in the science of clay interactions with biomolecules, polymers, and cells are examined, focusing on the implications for tissue engineering and regenerative strategies. Pioneering studies demonstrating the utility of clay for drug‐delivery and scaffold design are reviewed and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
252
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(259 citation statements)
references
References 165 publications
0
252
0
Order By: Relevance
“…In addition to osteoinductive properties, nanosilicates has been demonstrated to drastically improve mechanical properties of soft nanocomposite materials. [31,33] So we expect that the addition of nanosilicate to PGS will enhance the mechanical stiffness of nanocomposite network.…”
Section: Nanosilicate Enhances Mechanical Stiffness Of Nanocompositesmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to osteoinductive properties, nanosilicates has been demonstrated to drastically improve mechanical properties of soft nanocomposite materials. [31,33] So we expect that the addition of nanosilicate to PGS will enhance the mechanical stiffness of nanocomposite network.…”
Section: Nanosilicate Enhances Mechanical Stiffness Of Nanocompositesmentioning
confidence: 98%
“…[23,24] Some of the promising biomedical applications for nanosilicates-based composites include high-performance elastomers [25][26][27][28], selfhealing structures [29], injectable hemostats [30], moldable hydrogels [31], and drug delivery vehicles [32,33]. Recently, our group showed that by incorporating nanosilicates in collagen-based matrix, significant enhances alkaline phosphate (ALP) activity (an early marker for osteogenesis), and promotes production of mineralized matrix.…”
Section: Introductionmentioning
confidence: 97%
“…[1] In particular smectite clays which swell and delaminate into individual particles, can host an array of potential interactions with organic molecules on particle surfaces or within interlayer pores and inter-particle spaces through cation-exchange, hydrophobic interactions, hydrogen bonding, cation bridging, anion exchange and proton transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Clay-biomolecule interactions have been applied for delivery of drugs in tablet form through drying and compaction of clay-drug complexes, or else in polymer-clay nanocomposites developed for drug delivery and, more recently, tissue regeneration [1].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported by Ceyhan et al [20] that the cells in the body are not biologically significant influenced by the zeolite that has been incorporated in simulated body fluids. In its development, the zeolites have also been used as antidiarrheal drugs [21], the elimination of ammonia ions from renal dialysis and treatment of external wounds [22]. The favorable effects of zeolites in several conditions of a disease have been discussed [15,23].…”
Section: Introductionmentioning
confidence: 99%